66‐2: Comparison of Flat and Curved Monitors: Eyestrain Caused by Intensive Visual Search Task. Issue 1 (May 2016) - Luo, Gang; Chen, Ying; Doherty, Amy; Liu, Rui; Shi, Cong; Wang, Shuhang; Le, Hoai; Peli, Eli
Abstract : Twenty‐seven observers performed intensive visual search tasks with curved and flat monitors. Based on a 22‐item eyestrain questionnaire, fewer subjects reported eyestrain, difficulty‐to‐focus and blurred‐vision symptoms with a curved monitor than with a flat monitor. Fewer subjects had reduced saccade peak speed following the curved monitor use.